A experiência brasileira em avaliações de interesse público em defesa comercial: repercussões práticas do aperfeiçoamento regulatório ocorrido no período pós-2019 - Cavalcanti, Mariana Piccoli L. (2022)
This master thesis aims to evaluate Brazilian public interest regime in commercial defense, both from a procedural and material perspective, verifying if identified deficiencies were remedied by the regulatory changes promoted from 2019 (when there was a relevant change in the regulatory framework with the publication of Decree No. 9,679). Based on empirical research, in which objective criteria were adopted to identify public interest assessments completed in Brazil between January 2019 and October 2021, a descriptive analysis of said assessments was carried out, based on standardized parameters that avoid a subjective approach of the formal and material aspects adopted. The results obtained show that the regulatory changes promoted have brought considerable benefits to the Brazilian public interest institute in trade defense, but there are still, at least in part, criticisms related to procedural and material aspects.